MODERN LABORATORY DIAGNOSTICS OF BRONCHIAL ASTHMA - Mirzayev Otabek Sayfiddinovich; Isomadinova Lola Kamolidinovna; Yulayeva Irina Andreevna (Web of Journals Publishing, 2025)
According to the World Health Organization (WHO). Modern laboratory diagnostics play a crucial role in assessing disease severity, identifying its etiology, and monitoring treatment effectiveness. This article provides a detailed overview of methods for detecting inflammation biomarkers, specific IgE, eosinophils, fractional exhaled nitric oxide (FeNO), and the role of genetic studies. Recent advancements and their significance in a personalized approach to asthma management are discussed.
Keywords: Bronchial asthma, laboratory diagnostics, specific IgE, eosinophilia, FeNO, biomarkers, genetic studies, inflammation.